Manajemen Pondok Pesantren Salafi di Era Milenial - Muhamad Dini Handoko (Jurnal Dewantara, 2019)
This study aims to determine the evolution of the Salafi Islamic boarding school in this millennial era. The approach used in this study is a qualitative approach. The subject in this research is Riyadlatul Ulum Islamic Boarding School, Lampung Timur-Lampung. This cottage is one of the salafi huts in Lampung Province. To obtain the data the researchers conducted a direct observation method by directly involved in the activities of the lodge. In this case it was found that the salafi huts were also able to evolve by developing its curriculum in the study of language and the independence of its students. In languages, pesantren train their students to be able to preach using Arabic and English. Whereas in terms of independence, students are taught to become entrepreneurs using online media, but all this still maintains the wisdom of the pesantren salafi.